CRITICAL DISCOURSE ANALYSIS OF DUREX RED ADVERTISEMENT (SAVE VERSION) THROUGH NORMAN FAIRCLOUGH’S CDA - Ariza Purnawati; Fatwa Fathumakka (Asosiasi Dosen Muda Indonesia, 2022)
This research aims to find out the ideology contained in the Durex RED advertisement (save version) and the purpose of the advertisement for the use of contraceptives. Durex RED is a product created by combining the collaboration of Durex and RED as a fundraising association in the World AIDS Day in 2018. In this research, the researchers used Norman Fairclough's critical discourse analysis method by looking at the text on the advertisement based on three dimensions: text (text), text practice (discourse practice), and sociocultural practice (sociocultural practice). The results of the study found that by doing cooperation with RED and Zara Larsson in raising fund for charity, Durex RED advertisement encourages people around the world, especially in Europe, USA, and Greenland, to do safe sex, use condom, and help people in Africa to support World AIDS Day.